2010
DOI: 10.1002/cphc.201000484
|View full text |Cite
|
Sign up to set email alerts
|

Surface Species Alteration and Oxygen Reduction Reaction Enhancement of PdCo/C Electrocatalysts Induced by Ceria Modification

Abstract: The effect of reduction temperature and CeO2 addition on the activity of PdCo/C alloy catalysts (see scheme) toward the oxygen reduction reaction (ORR) is investigated. By combining X‐ray analysis and temperature‐programmed reduction with electrochemical measurements, the relationship between phase structure, surface information and catalytic activity toward ORR of the non‐Pt PdCo catalysts is elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Moreover, if the I -03 and I peak values of various catalysts shown in Table 2 are compared, two maximum for Ce 5 and Ce 15 are noted. It has been reported that CeO 2 can act as surface modifiers and/or texture promoters of the catalysts [9,10,35,37,42]. For Ce 5 , the addition of 5 wt.% CeO 2 can enrich the surface states with PdNi alloy species significantly and promote the dispersion of NPs on the support slightly.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Moreover, if the I -03 and I peak values of various catalysts shown in Table 2 are compared, two maximum for Ce 5 and Ce 15 are noted. It has been reported that CeO 2 can act as surface modifiers and/or texture promoters of the catalysts [9,10,35,37,42]. For Ce 5 , the addition of 5 wt.% CeO 2 can enrich the surface states with PdNi alloy species significantly and promote the dispersion of NPs on the support slightly.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, it is important to mention that the T r of Ce x (x = 10-20) samples slightly moves back to T < 272 K, indicating that the surface AO x species is intensively converted to metallic surface Pd species while in the CO-stripping results, the pre-wave disappears consistently. Even though CeO 2 acts as a textural promoter and surface modifier which change the dispersion and surface composition of alloy NPs, the excessive Ce addition may retard the complete reduction of the Pd or Ni metal ions [40,42] and block the active sites. As a consequence, the change of surface species and the presence of NiO species are manifestly observed for Ce x (x = 10, 15, and 20) samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations